Back to basics with newer technology: Should we focus on reducing work of breathing earlier? - Sciarretta, Christopher; Greenberg, Jeremy; Wyatt, Kara D.; Whittle, Jessica S. (Frontiers in Medicine, 2022)
The typical approach to management of respiratory distress is focused on oxygen supplementation. However, additional oxygen alone does not improve outcomes, particularly in critically ill patients. Instead, supplemental oxygen can be associated with increased morbidities. We present the hypothesis that clinicians should focus on reducing the work of breathing early in the course of critical illness. Rather than simply supplementing oxygen, newer technologies including high flow nasal oxygen, may be utilized to increase the efficiency of gas exchange. By reducing the work of breathing, the cardiac workload can be reduced, thus relieving some excess physiologic stress and supporting the critically ill patient. To illustrate this point, we provided three clinical cases of respiratory failure from non-pulmonary origins; all cases displayed hemodynamic improvement due to reducing the work of breathing through high-velocity therapy prior to receiving definitive therapy for underlying pathologies.